Care and Community Empowerment: Coalition-Building Between Home Care Workers and Disability Rights Activists - Kozak-Oxnard, Andrea (Columbia Journal of Gender and Law, 2017)
This Note looks closely at the issues facing home care workers and the persons with disabilities and older persons who consume that care. It argues that without seriously taking into account the unique intersectional needs of both care providers—predominately low-income women of color—and care consumers—generally persons who have disabilities, are elderly, or both—advocates will fail to create empowering care partnerships. The Note discusses the ways in which a purely feminist or disability rights lens fails to take into account the complex dynamics of the home care relationship, and suggests that scholars who have integrated the needs of care workers and care consumers have provided what should be considered foundational theories for home care empowerment activism. It implores advocates to continue to look to theorists that holistically incorporate feminist scholarship and disability rights scholarship in order to best understand the complex, multi-dimensional issues facing participants to relationships of care. The Note also examines advocates and organizations already doing this kind of integrated work and argues that they should be promoted and emulated, to the extent that their efforts have been successful. Finally, the Note lays out several possible policy solutions that would serve the needs of home care workers and care consumers, empowering and elevating all care participants, and contends that these should be prioritized in advocacy efforts going forward.